4.3: Ultra‐Thin LTPS‐TFT LCD by Using Glass‐on‐Carrier Technology. Issue 1 (June 2015) - Chiao, Shun‐Ping; Fan, To‐Cheng; Chan, Chun‐Hsiang; Liao, Chi‐Hong; Lai, Ying‐Hui; Lu, Jen‐Kuei; Sugiura, Norio
Abstract : A glass on carrier technology was developed and applied to low temperature poly‐silicon (LTPS) TFT‐LCD. A newly optimized debonding layer SION successfully provided easily peeling of the glass from the carrier even after LTPS high temperature process. Finally an ultra thin LTPS TFT‐LCD whose total thickness is 0.915mm was realized by the glass on carrier technology.